The Effectiveness of Prevention and Relationship Enhancement Program (PREP) on Marital Burnout in Married Women - Mikaeili , Niloofar; Aghajani , Seifollah; Habibi , Narges; Fathi , Elham; Hatami Varzaneh, Abolfazl (Shahroud Journal of Medical Sciences, 2021)
Background: This study aimed to investigate the effectiveness of the prevention and relationship enhancement program (PREP) on marital burnout in married women.Methods: Thirty married women were selected and randomly replaced in experimental (n=15) and control (n=15) groups. The quasi-experimental research method was conducted in the pretest-posttest control group design to examine the effectiveness of the PREP on marital burnout in married women. The sessions of the PREP were implemented for the experimental group during 8 sessions of 90 minutes, one session per week, and no educational intervention was performed for the control group. Multivariate analysis of covariance was used as a statistical method.Results: The results showed that there was a significant difference between the control and experimental groups in psychological and emotional aspects of marital burnout(Pvalue≤0.02). Our results also showed that the total burnout score was significantly different from pre-test to post-test in the experimental group (Pvalue≤0.01).Conclusions: It can be implied from the results of our study that PREP can have different implications in Iranian culture.Keywords: Prevention and Relationship Enhancement Program (PREP), Marital Burnout, Married Women.